Efeito do butafosfan no metabolismo de vacas leiteiras saudáveis ou com mastite clínica - Tabeleão, Vinícius Coitinho (2014)
Dairy cows are expected to perform maximum of their productive capacity, especially during the transition period (three weeks before and up to three weeks after calving). This period is characterized by intense changes in metabolism which cause a negative energy balance. This fact generates a period of typical weight loss, which has been correlated with insulin resistance, once the available glucose is destined for lactose synthesis, which in turn is responsible, in part, for milk production levels. Moreover, during lactation there are several managements that impairs animals health. If not executed properly, can cause trauma and predisposition for infections, especially of the mammary gland, because this gland is heavily manipulated and has contact with potentially infectious agents. From a entrance doorway, these agents can infect the gland and cause mastitis, which may be clinical (with clinical signs) or subclinical (without clinical signs). In situations of metabolic disorders or in cases of mastitis, the milk production may be affected. Therefore, there is a constant search for technologies that can minimize these disorders and assist the production systems. Our objective was to investigate the effects of combining butaphosphan and cyanocobalamin on the glycemic metabolism in healthy dairy cows in the postpartum period and their effects on the mammary gland recovery in dairy cows after clinical mastitis treatment. Thus, our study was stratified into two assumptions: 1) the use of the association of butaphosphan and cyanocobalamin enhances peripheral insulin resistance in dairy cows, providing greater amounts of glucose for milk production, 2) the supplementation with butaphosphan and cyanocobalamin facilitates mammary gland recovery in dairy cows affected by mastitis. In experiment 1, animals receiving repeated doses of butaphosphan and cyanocobalamin had greater weight loss and increased (P<0.05) of the activities of the enzymes aspartate aminotransferase and creatine kinase. Moreover, at end of treatment had an increase (P<0.05) in glucose concentration in treated animals when compared to the beginning of study. In experiment 2, the comparative analyzes between mild and moderate mastitis did not differ (P>0.05) in any parameters. The animals treated with butaphosphan and cyanocobalamin had lower (P<0.05) somatic cell count after the third application. However, the concentrations of glucose, albumin, TPP, NEFA and the chemical and physical components of milk did not differ (P>0.05) among groups. In concusion, the combination of butaphosphan and cyanocobalamin shows promising results as a source of nutrient that allows intensify physiological reactions mainly dependent phosphorylation.